2005
DOI: 10.1016/j.visres.2004.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic properties of the colour-shading effect

Abstract: The 'colour-shading effect' describes the phenomenon whereby chromatic variations affect the magnitude of perceived shape-from-shading in luminance patterns. A previous study showed that in mixed colour-plus-luminance sine-wave plaids, impressions of depth in the luminance component were enhanced by non-aligned chromatic components, and suppressed by aligned chromatic components [Nature Neuroscience 6 (2003) 641-644]. Here we examine the chromatic determinants of these effects. Colour contrast was defined alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 27 publications
3
36
1
Order By: Relevance
“…However, this choice of HM grating was arbitrary. Kingdom et al (2005) showed that the colour direction of both the depth-enhancing and depth-suppressing chromatic gratings in the colour-shading effect was unimportant: it was their colour contrast that mattered. For this reason the details of the generation of the HM grating will not be given here, but the interested reader can consult the aforementioned article.…”
Section: Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…However, this choice of HM grating was arbitrary. Kingdom et al (2005) showed that the colour direction of both the depth-enhancing and depth-suppressing chromatic gratings in the colour-shading effect was unimportant: it was their colour contrast that mattered. For this reason the details of the generation of the HM grating will not be given here, but the interested reader can consult the aforementioned article.…”
Section: Stimulimentioning
confidence: 99%
“…The 'colour-shading effect' (Kingdom, 2003;Kingdom et al, 2005) is a recent example of this approach. When a chromatic grating is added to a differentlyoriented luminance grating, one obtains an impression of a corrugated surface -an instance of 'shape-from-shading'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our brains do not rely on the physics of the real world to interpret shadows [29]. Furthermore, our brains do not even require the wavelength composition of shadows to be consistent with plausible illumination conditions: We simply require local regions to be relatively darker, and of relatively desaturated color [30]; in fact, the shadow itself can be of any color as long as these rules are met, as the Fauvists showed, and Kingdom et al recently confirmed [31].One reason why shadows, perspective, and reflection may not need to be physically accurate for an acceptable impression of depth, transparency, or shine is that the visual system evolved under conditions in which these features are not stable and not consistent within a scene over time: Shadows change as daylight changes (hence the inconsistencies of shadows in impressionist paintings, which were often painted outdoors over a stretch of time during which the sun and shadows move); similarly, perspective and reflections change second to second as we move our eyes across a scene. Therefore, there would have been little biological benefit to incorporate the rules for global perspective or illumination into our visual computations.…”
mentioning
confidence: 97%
“…Therefore, our brains do not rely on the physics of the real world to interpret shadows [29]. Furthermore, our brains do not even require the wavelength composition of shadows to be consistent with plausible illumination conditions: We simply require local regions to be relatively darker, and of relatively desaturated color [30]; in fact, the shadow itself can be of any color as long as these rules are met, as the Fauvists showed, and Kingdom et al recently confirmed [31].…”
mentioning
confidence: 98%